2017
DOI: 10.1177/0363546517708192
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Chondral Lesions in Hip Arthroscopy: Relationships Between Grade, Topography, and Demographics

Abstract: Higher grades of acetabular chondral damage were related to male sex, increased age, height, weight, BMI, and the size of the lesion. Chondral lesions were generally found in the anterosuperior region of the acetabulum, consistent with labral lesions and the weightbearing area of the acetabulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 15 publications
(16 reference statements)
3
51
0
3
Order By: Relevance
“…Our findings are supported by previous studies that similarly demonstrated that male sex, older age, and elevated alpha angles were independently associated with the presence of acetabular damage during hip arthroscopic surgery. 23 , 34 , 38 Despite these findings, labral tearing and chondral damage seen intraoperatively did not correlate with PRO scores. While these results may seem counterintuitive, they are consistent with the findings of Westermann et al, 36 who showed that HOOS scores did not correlate well with macroscopic findings of damage during hip arthroscopic surgery for patients with FAI and that these scores correlated better with mental health, activity levels, and smoking status.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings are supported by previous studies that similarly demonstrated that male sex, older age, and elevated alpha angles were independently associated with the presence of acetabular damage during hip arthroscopic surgery. 23 , 34 , 38 Despite these findings, labral tearing and chondral damage seen intraoperatively did not correlate with PRO scores. While these results may seem counterintuitive, they are consistent with the findings of Westermann et al, 36 who showed that HOOS scores did not correlate well with macroscopic findings of damage during hip arthroscopic surgery for patients with FAI and that these scores correlated better with mental health, activity levels, and smoking status.…”
Section: Discussionmentioning
confidence: 79%
“…20 Reduced hip extension during walking is also commonly seen in patients with early hip OA 46 and is thought to be a compensation strategy to unload the anterior hip joint, 24 the common location of chondrolabral abnormalities associated with FAIS. 36 It is important to note that HA for FAIS changes hip morphology, but much of the intra-articular abnormality remains. More than 80% of all patients in this study had acetabular cartilage defects during the time of arthroscopic surgery, which is a common finding in comparable cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Concomitant acetabular chondral lesions are a common finding in patients with femoroacetabular impingement undergoing hip arthroscopy, with rates ranging from 80% to 100% of patients. [22][23][24][25] This discrepancy between imaging and arthroscopy reduces our ability to have appropriate preoperative discussions with patients about their pathology and treatment options. It also limits our ability to have the appropriate chondral transplantation equipment available.…”
Section: Discussionmentioning
confidence: 99%